An Investigation of the Effectiveness of Super White Cement in Improving the Engineering Properties of Organic Soils by Laboratory Tests - Avci, Eyubhan; Balci, Mehmet C.; Toprak, Muhammed A.; Uysal, Melih; Deveci, Emre; Karatas, Gozde Algun; Donertas, Yunus E. (Mdpi, 2025)
In this study, the efficacy of super white cement (SWC) to improve organic soils was researched. For stabilization, 10%, 15%, and 20% proportions of SWC were added to organic soil. After improvement with SWC, Atterberg limit testing, standard Proctor tests, triaxial compression tests, and swelling and compressibility tests were performed on the organic soil. Proctor tests showed that stabilization of organic soil with SWC increased maximum dry density (MDD) and optimum moisture content (OMC) values. After stabilization, the unconfined compressional strength values of the soil increased. This increase continued until the 28th day and had a reducing trend after improvement with SWC, linked to time. In addition to the reaction between SWC and OS, the time-dependent behavior of OS also contributed to this behavior. With the increase in SWC proportions, the cohesion intercept and internal friction angle values rapidly increased until the 56th day. This increase began to reduce after the 56th day. After stabilization, the swelling percentage and compressibility values for the soil reduced. The addition of SWC within organic soil appeared to improve the engineering properties of the soil.
Keywords: cement; super white cement; soil stabilization; ground improvement; organic soils; strength